Physical activity in healthy, older people. How many drops of sweat away from gain the health benefit? - Kujawska, Agnieszka; Perkowski, Radosław; Androsiuk-Perkowska, Joanna; Skierkowska, Natalia; Gajos, Małgorzata; Topka, Weronika; Kujawski, Sławomir; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2017)
Introduction: Aging process leads to increased risk of functional impairments and diseases occurrence. Sedentary lifestyle is one of the main risk factors the occurrence of chronic disease such a diabetes and cardiovascular disease. On the other hand, results of many studies showed that regular physical activity (PA) and physical exercise (PE) could decrease the risk of these hazards. Last decades were fruitful in developing evidence-based recommendations for physical activity and exercise in older people, therefore it is worth to examine dynamics of development and the similarities between different recommendations. Material and methods: Articles in the EBSCO database have been analyzed using keywords: older people, physical exercise, physical activity, recommendations, aerobic training, resistance training. Results: Studies showed that people who were more active during lifetime, have greater self-efficacy, better physical and mental health status and in general higher satisfaction on the autumn of their life. Every analyzed recommendation underlies the negative consequences of sedentary activity, however, there is no evidence-based “cut-off” point. Similarly, there is not clear optimal “dose” of PA or PE to prescribe for older patients. Conclusions: It seems that undertaking light level of PA activity is more beneficial than none PA or sedentary lifestyle. The newest recommendations underlie the possibility of the existence of positive linear relationship between the level of PA and health benefits: every additional amount of time spent on PA during week could be related with additional health benefit